Thermal emission by a subwavelength aperture. (April 2016) - Joulain, Karl; Ezzahri, Younès; Carminati, Rémi
Abstract: We calculate, by means of fluctuational electrodynamics, the thermal emission of an aperture separating from the outside, vacuum or a material at temperature T . We show that thermal emission is very different whether the aperture size is large or small compared to the thermal wavelength. Subwavelength apertures separating vacuum from the outside have their thermal emission strongly decreased compared to classical blackbodies which have an aperture much larger than the wavelength. A simple expression of their emissivity can be calculated and their total emissive power scales as T 8 instead of T 4 for large apertures. Thermal emission of disk of materials with a size comparable to the wavelength is also discussed. It is shown in particular that emissivity of such a disk is increased when the material can support surface waves such as phonon polaritons. Abstract : Highlights: We calculate thermal emission of an aperture smaller than the thermal wavelength. Subwavelength thermal aperture emissive power scales as T 8 instead of T 4 . In the case of a geometrical surface S supporting polaritons, thermal emission can exceed Ss T 4 .